E-contract Consensus in Indonesian Contract Law - Sulistyaningrum, Helena Primadianti (Batulis Civil Law Review, 2024)
Introduction: In the era of Society 5.0, the use of IT in implementing agreements in Indonesia is inevitable. The development of e-contracts, becoming increasingly necessary in society, is demanding the business world's attention. Particularly in Indonesia's Treaty Law, the concept of consensual e-contracting emerged, suggesting that even in the absence of direct meetings, parties could still realize an agreement through the e-contract. Purposes of the Research:  This study aims to analyze and describe the existence of e-contract consensus in contract law in Indonesia from the point of view of contract theory. Methods of the Research: This specific type of investigation is doctrinal law research, which endeavors to uncover the truth by employing legal principles, foundational doctrines, and doctrinal law as supporting material. This work utilizes an inductive methodology, first presenting specific assertions and then drawing a general conclusion from them.Results of the Research: One of the legal prerequisites for an agreement is consensus. The study's findings indicate that legislative regulations in Indonesia have incorporated e-contract consensus into contract law. We apply Uitings theory, Verzending theory, and Ontvangs theory as agreement theories to determine the existence of e-contract consensus. The legislation contains provisions that specifically address the maintenance of electronic transactions. In general, it establishes that an electronic transaction has taken place when the parties to an electronic contract (e-contract) issue a statement of acceptance of an offer.